SraTailor: Graphical user interface software for processing and visualizing ChIP‐seq data. (17th October 2014) - Oki, Shinya; Maehara, Kazumitsu; Ohkawa, Yasuyuki; Meno, Chikara
<x xml:space="preserve">Abstract</x> Raw data from ChIP‐seq (chromatin immunoprecipitation combined with massively parallel DNA sequencing) experiments are deposited in public databases as SRAs (Sequence Read Archives) that are publically available to all researchers. However, to graphically visualize ChIP‐seq data of interest, the corresponding SRAs must be downloaded and converted into BigWig format, a process that involves complicated command‐line processing. This task requires users to possess skill with script languages and sequence data processing, a requirement that prevents a wide range of biologists from exploiting SRAs. To address these challenges, we developed SraTailor, a GUI (Graphical User Interface) software package that automatically converts an SRA into a BigWig‐formatted file. Simplicity of use is one of the most notable features of SraTailor: entering an accession number of an SRA and clicking the mouse are the only steps required to obtain BigWig‐formatted files and to graphically visualize the extents of reads at given loci. SraTailor is also able to make peak calls, generate files of other formats, process users' own data, and accept various command‐line‐like options. Therefore, this software makes ChIP‐seq data fully exploitable by a wide range of biologists. SraTailor is freely available at http://www.devbio.med.kyushu-u.ac.jp/sra_tailor/, and runs on both Mac and Windows machines.